Nurses' Perspectives on Causes of Medication Errors and Non- Reporting at ED. - Salavati S; Hatamvand F; Tabesh H; Salehi nasab M (Iran University of Medical Sciences, 2012)
Background & Aims: Medication errors caused by healthcare providers can seriously threat patients' health. The first step to present strategies for preventing such incidents is to assess the causes of errors and non- reporting. The purpose of this study was to investigate the causes of medication errors and lack of their reporting from the perspective of nurses working in the emergency department.   Material & Methods: In this descriptive cross-sectional study, 71 nurses working in the emergency departments of five teaching hospitals in Ahvaz city were selected by census. Data were gathered by questionnaire. The questionnaire was consisted of three sections including demographic characteristics, questions about the importance of causes of medication errors, and causes of non- reporting. Data was analyzed by descriptive statistics using SPSS-PC (v.16).   Results: The most important causes of medication errors were occupational fatigue exhaustion , low nurse to patient ratio , large number of critically-ill patients , long working hours, high density of work in units and doing other tasks simultaneous ly with drug administration respectively. The most important cause of non-reporting was "managerial factor" (4.12±0.76). In this respect, "not receiving positive feedback for reporting medication error s" (4.33±0.90) and " managers ' concentration on individual factors rather than system factors as the potential causes of error s" (4.30±0.93) were the most important causes for non- reporting from nurses perspective.  Conclusion: Working condition in the emergency department including nurses' workload and the number of patients cared by nurses are important in the development of preventable medication errors. Positive feedback after error reporting and determination of error s causes can persuade nurses for error reporting.  Received: 5 Dec 2012   Accepted: 27 Feb 2013